Purification and Characterization of Carbazole 1,9a-Dioxygenase, a Three-Component Dioxygenase System of Pseudomonas resinovorans Strain CA10 - Nam, Jeong-Won (American Society for Microbiology, 2002)
The carbazole 1,9a-dioxygenase (CARDO) system of Pseudomonas resinovorans strain CA10 consists of terminal oxygenase (CarAa), ferredoxin (CarAc), and ferredoxin reductase (CarAd). Each component of CARDO was expressed in Escherichia coli strain BL21(DE3) as a native form (CarAa) or a His-tagged form (CarAc and CarAd) and was purified to apparent homogeneity. CarAa was found to be trimeric and to have one Rieske type [2Fe-2S] cluster and one mononuclear iron center in each monomer. Both His-tagged proteins were found to be monomeric and to contain the prosthetic groups predicted from the deduced amino acid sequence (His-tagged CarAd, one FAD and one [2Fe-2S] cluster per monomer protein; His-tagged CarAc, one Rieske type [2Fe-2S] cluster per monomer protein). Both NADH and NADPH were effective as electron donors for His-tagged CarAd. However, since the k(cat)/K(m) for NADH is 22.3-fold higher than that for NADPH in the 2,6-dichlorophenolindophenol reductase assay, NADH was supposed to be the physiological electron donor of CarAd. In the presence of NADH, His-tagged CarAc was reduced by His-tagged CarAd. Similarly, CarAa was reduced by His-tagged CarAc, His-tagged CarAd, and NADH. The three purified proteins could reconstitute the CARDO activity in vitro. In the reconstituted CARDO system, His-tagged CarAc seemed to be indispensable for electron transport, while His-tagged CarAd could be replaced by some unrelated reductases.